The role of blockchain in mitigating financial fraud: a paradigm shift in accounting practices - Safeei, Roshidah (Universiti Teknologi MARA, Kedah, 2025)
In the modern financial landscape, the prevalence of financial fraud continues to undermine trust, transparency, and the credibility of institutions worldwide. According to the Association of Certified Fraud Examiners (ACFE) (2024), global organizations lose approximately 5% of their annual revenues to fraud, amounting to trillions of dollars each year. The interconnected nature of global markets and the digitization of financial processes have created vulnerabilities for fraudulent activities such as asset misappropriation, financial statement manipulation, and cyberattacks. Traditional accounting and auditing systems, while evolving, often struggle to keep pace with the sophisticated tactics employed by fraudsters. These challenges have prompted researchers and practitioners to explore innovative technologies, with blockchain emerging as a potential game-changer in mitigating financial fraud. Blockchain technology, with its decentralized, immutable, and transparent architecture, offers significant potential to address systemic weaknesses in accounting and fraud prevention. By securely recording transactions on a distributed ledger, blockchain eliminates the risk of unauthorized modifications to financial records. Its ability to provide real-time audit trails and enforce compliance through smart contracts enhances its appeal as a tool for building trust and accountability in financial systems. Moreover, blockchain's applications extend beyond fraud detection, enabling advancements in financial reporting, supply chain accounting, and regulatory compliance.